A Literature Review: Analysis of Clinical Pathway Implementation for Covid-19 Patients - Chohan, Zakir; Syarif, Syahrizal; Sudaryo, Mondastri Korib (Global Health Science Group, 2024)
Clinical pathway is a guideline for evidence-based medical care, best service, patient expectations for communication facilities, multidisciplinary activities, patients, families, as documentation, monitoring, recording, variants, providing the necessary resources and results. Objective to determine the extent to which the implementation of the clincal pathway is applied and is beneficial to Covid-19 patients.Method: The method used was to conduct a critical analysis of research articles, regarding the implementation of clinical pathways for Covid-19 patients during the pandemic taken from the Pub Med and PMC databases with the keywords used: Implementation AND clinical pathway AND Covid-19 AND pandemic. The number of articles analysed was 116 and then obtained 3 relevant articles. Results: Clinical pathway is useful in facilitating the lack of access to patient examination services, supporting examinations, and also treatment. Clinical pathways that are incorporated into E-medical records help clinicians to get the latest information and improve adherence to evidence-based guidelines so as to produce good results for services. Clinical pathways are needed as guidelines in the application of diagnostic and management of Covid-19 disease in children.Conclusion: Clinical pathway implementation is needed in services, especially in access gaps, up-to-date information, clinician compliance, diagnostic guidelines and management of Covid-19 patients to get good evidence-based.